Strengthening the Usaha Tani group Nagari Sungai Abang as organic center in Subdistrict of Lubuk Alung Padang Pariaman - Kardiman, Reki; Achyar, Afifatul; Selaras, Ganda Hijrah; Novita, Yeni; Fardilla, Midratul; Roza, Sri Yenica (Pelita Eksakta, 2025)
Back to organic farming is necessary but applying this should begin with production of the organic products in a special place called organic center, where the all possible organic products produced from organic waste in a place. This approach has started by the Usaha Tani group last year but failed in fulfilling the goals. This program was proposed to strengthening the organic center with some simple organic projects such as liquid organic fertilizer (LOF), eco-enzyme and maggot. The activities were conducted through establishing the facilities and enhancing the skills. Three of 100 kg buckets were established and were produced about 60 liter LOF, and eco-enzyme is now producing about 1680 liter within 15 of 25 kg buckets, while 450 maggots were ready to be released for making hundred thousand eggs. The farmer group is very antusias with the process and the promissing yields, and be ready for the next steps.